An analysis of the Murabahah Islamic Finance Instrument in the context of article 11 of the OECD model tax convention on income and capital - Sahabodien, Waleed (Department of Commercial Law, 2019)
Conventional banking and finance is based on interest-bearing loans or investments, or equity financing arrangements. Islamic banking and finance provides equivalent functionality to conventional finance except that the underlying arrangement is based on the trading of assets, profit and loss sharing investments or leasing arrangements. International business and trade has evolved over time and contemporary transactions and methods of providing cross-border funding has undoubtedly become more fluid and complex in this regard. So much so that non-traditional sources of financing have become more prominent as a viable alternative where we have seen a considerable increase in their use. This is evident with the steady growth and expansion of Islamic finance within the wider umbrella of the ‘Islamic Economy’. Importantly, multi-national enterprises are indeed open to diversifying their funding. This is however complimentary to the primary demand for these services from a growing global Muslim population. Article 11 governs the taxation of cross-border debt financing where the focus is in essence on the taxing rights allocated between the source and resident state respectively. In practice it appears to be a rather settled article where very few meaningful amendments have been made since its inception. The formulation and policy is based on historical factors and an agreed upon balance established at that time. With the introduction of non-traditional financial arrangement such as Islamic finance, we now perhaps see this historical balance being somewhat disturbed. It is important to note that it is an express purpose of international tax treaties to facilitate cross-border trade and ensure the economic exchanges are as seamless as possible in respect of taxation matters. Whether the incorporation of non-traditional financial instruments in article 11 could indeed reduce the risk of double taxation or double-non taxation remains to be seen, and it is not the objective of this paper to speculate on these aspects. Rather, this dissertation seeks to analyse the position of Islamic finance with regards to the Organisation for Economic Co-operation and Development “OECD” Model Tax Convention and whether uncertainty is created under article 11 and a ‘debt-claim’.